2011
DOI: 10.1007/s00774-011-0329-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Escherichia coli-produced recombinant human bone morphogenetic protein 2 on the regeneration of canine segmental ulnar defects

Abstract: Because bone morphogenetic protein 2 gene transfected Escherichia coli (E-BMP-2) produce recombinant human BMP-2 (rhBMP-2) more efficiently than mammalian cells (Chinese hamster ovary [CHO]-BMP-2), they may be a more cost-effective source of rhBMP-2 for clinical use. However, use of E-BMP-2 for regenerating long bones in large animals has not been reported. In the current study, we evaluated the healing efficacy of E-BMP-2 in a canine model. We created 2.5-cm critical-size segmental ulnar defects in test anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…CHO cell‐ and E. coli‐ derived rhBMP‐2 have been shown to induce comparable dose‐dependent ectopic bone formation after intramuscular implantation in rodent screening models, suggesting E. coli ‐derived rhBMP‐2 to be a realistic alternative to CHO cell‐derived rhBMP‐2 26,27 . Nevertheless, the efficacy of E. coli ‐derived rhBMP‐2 in large‐animal, orthotopic, clinically relevant settings has received limited attention 28,29 . Therefore, the objective of this study is to evaluate local bone formation and dental implant osseointegration in conjunction with alveolar augmentation using E. coli ‐derived rhBMP‐2 and compare to the benchmark CHO cell‐derived rhBMP‐2 using an established large‐animal model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHO cell‐ and E. coli‐ derived rhBMP‐2 have been shown to induce comparable dose‐dependent ectopic bone formation after intramuscular implantation in rodent screening models, suggesting E. coli ‐derived rhBMP‐2 to be a realistic alternative to CHO cell‐derived rhBMP‐2 26,27 . Nevertheless, the efficacy of E. coli ‐derived rhBMP‐2 in large‐animal, orthotopic, clinically relevant settings has received limited attention 28,29 . Therefore, the objective of this study is to evaluate local bone formation and dental implant osseointegration in conjunction with alveolar augmentation using E. coli ‐derived rhBMP‐2 and compare to the benchmark CHO cell‐derived rhBMP‐2 using an established large‐animal model.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 Nevertheless, the efficacy of E. coli-derived rhBMP-2 in large-animal, orthotopic, clinically relevant settings has received limited attention. 28,29 Therefore, the objective of this study is to evaluate local bone formation and dental implant osseointegration in conjunction with alveolar augmentation using E. coliderived rhBMP-2 and compare to the benchmark CHO cell-derived rhBMP-2 using an established large-animal model.…”
mentioning
confidence: 99%
“…[17] The production of recombinant BMP-2 from Escherichia coli (eBMP-2) has facilitated production of large quantities of the protein at a relatively lower cost. [23] Pitfalls Many benefits are associated with the use of rhBMP-2, but it is not free of complications, as summarised in Table 2. Studies show they are safe when used for 'on-label' conditions, but risks develop when used for 'off-label' conditions.…”
Section: Costmentioning
confidence: 99%
“…[41] Another study explored the use of Escherichia coli produced rhBMP-2 in canines, as E. coli produced rhBMP-2 more efficiently than mammalian cells. [23] This study focused on the healing efficacy of this particular type of BMP-2 and found that the concentration of BMP-2 delivered affected the healing efficacy, with higher concentrations displaying more osteogenesis and a more pronounced bone regeneration. [23] Using E. coli-derived BMP-2 (eBMP-2) may be more cost-effective and efficient as a source of rhBMP-2 for clinical use.…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation